Association Between Plasma Monocyte Trafficking-Related Molecules and Future Risk of Depression in Older Adults. Issue 9 (6th July 2021) - Oh, Dae Jong; Bae, Jong Bin; Kim, Tae Hui; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Moon, Seok Woo; Park, Joon Hyuk; Ryu, Seung-Ho; Youn, Jong Chul; Lee, Dong Young; et al.
Abstract: Background: The recruitment of monocytes to the brain plays an important role in the development of depression. However, the association between plasma biomarkers of monocyte trafficking and depression is unclear. This study is aimed to examine the effects of plasma monocyte chemoattractant protein 1 (MCP-1), intercellular adhesion molecule 1 (ICAM-1), and vascular cell adhesion molecule 1 (VCAM-1) on the risk of depression. Methods: Data were acquired from an ongoing prospective cohort study involving randomly sampled, community-dwelling Korean older adults, which has been followed every 2 years. We included 1539 euthymic older adults (age = 68.2 [5.6] years; 51.7% were women) without a history of major psychiatric disorders and dementia and neurological diseases. Geriatric psychiatrists diagnosed incident depression through a structured interview using the Korean version of the Mini-International Neuropsychiatric Interview. Results: Depression had developed in 134 (8.7%) participants during the follow-up period of 5.7 (0.8) years. The high-plasma MCP-1 tertile group showed twofold higher risk of depression than the low-plasma MCP-1 tertile group (hazards ratio = 2.00, 95% confidence interval = 1.27–3.13, p = .003). The association between high levels of plasma MCP-1 and future risk of depression was significant in the middle-plasma ICAM-1 and VCAM-1 tertile groups; the high-plasma MCP-1 tertile group showed about fourfold higher risk of depression than the low-plasma MCP-1 tertile group. Conclusions: Molecules involved in monocyte trafficking may be good candidates as diagnostic biomarkers and/or therapeutic targets for late-life depression.